KONSEP WADRIBUHUNNA DALAM QS. AN-NISA' [4] : 34 STUDI KOMPARASI WAHBAH ZUHAILI DAN M. QURAISH SHIHAB - Fathollah, Moh. Fauzan (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Da'wah of IAIN Langsa, 2020)
Nushuz is a wife's that disobedience to the husband. Nushuz?s wife to the husband mentioned in QS. An-Nisa' [4] : 34. Indirectly in that verse also has been mentioned in tandem with a way to educate the wife of the nushuz. Many of the differences mentioned by the commentators to provide solutions regarding the wife who is nushuz. But, what is at the heart of the settlement is the final method, wadribuhunna (hitting). The concept of wadribuhunna mentioned by Wahbah Zuhaili is to beat by not injuring his wife while the concept of wadribunna. Muhammad Quraish Shihab is to look at the situation between men and women today, which is equal, so hitting is not the last way, but the right way is to give a gesture that can provide subtle education to wives who are nushuz. However, the two commentators have the same goal of the meaning of wadribuhunna, namely to apply the concept of islah that exists in the area of ??distribution of each interpretation.